Edukasi Bahasa Inggris Dasar Dan Mengenal Jajanan Sehat Dalam Bahasa Inggris Bagi Anak-Anak Tk Permata Bunda Banjarbaru - Risa Marina, Evi; Sajidah, Ainun; Hammad, Hammad; Zainab, Zainab; Ramie, Agustine; Erminawati, Erminawati (Jurnal Pengabdian Kepada Masyarakat Pusat Unggulan Iptek Penanggulangan Stunting Berbasis Kesehatan Ibu dan Anak, 2024)
Permata Bunda Sungai Ulin Kindergarten Banjarbaru has 33 students with group A as many as 10 people and group B as many as 23 people. The results of interviews with teachers and the principal of the kindergarten obtained data that there has been no Basic English learning and healthy snacks in English for children. Basic English training activities for children are designed to be held in one study group with basic English material content that is appropriate for the level of children. The methods used were lectures, questions and answers, and English language skills practice. This activity was conducted for 2 meetings. The first meeting was basic English education and healthy snacks in English. The second meeting was a re-learning (drill) of Basic English education and healthy snacks in English. The results showed that most of the students at Permata Bunda Kindergarten Sungai Ulin Banjarbaru had an increased level of knowledge after being given education about Basic English (greeting, colors) and healthy snacks in English, namely 23 people (69.6%) who had a good level of knowledge. This community service activity can increase the knowledge of Permata Bunda Sungai Ulin Banjarbaru Kindergarten students about Basic English (greeting, colors) and healthy snacks in English by 69.6%. In addition, this community service activity provides an alternative to learning Basic English to kindergarten students, and this community service activity also provides knowledge about healthy snacks for kindergarten children in English